Teks Efektif STPM : BAHASA MELAYU. - Azahar Bahari, author; Wardatul Hamra', author; Suhaimi Mohd. Salleh, author; Shamsul Mardiyyah Bahrum, author; Nur Hasliza Harun, editor (Petaling Jaya, Selangor : Penerbit Ilmu Bakti Sdn. Bhd., 2018)
PSZJBL